Acute oral toxicity, apoptosis, and immune response in nurse bees (Apis mellifera) induced by flupyradifurone - Gao, Jing; Guo, Yi; Chen, Jin; Diao, Qing-Yun; Wang, Qiang; Dai, Ping-Li; Zhang, Li; Li, Wen-Min; Wu, Yan-Yan (Frontiers in Physiology, 2023)
The potential toxicity of flupyradifurone (FPF) to honey bees has been a subject of controversy in recent years. Understanding the effect of pesticides on nurse bees is important because the fitness of nurse bees is critical for in-hive activities, such as larval survival and performing hive maintenance. In order to evaluate the acute oral toxicity of flupyradifurone on nurse bees, flupyradifurone at five different concentrations was selected to feed both larvae and nurse bees. Our results showed that nurse bees were more sensitive to flupyradifurone than larvae (LD50 of the acute oral toxicity of flupyradifurone was 17.72 μg a.i./larva and 3.368 μg a.i./nurse bee). In addition, the apoptotic rates of neurons in mushroom bodies of nurse bees were significantly induced by flupyradifurone at sublethal concentrations (8 mg/L, 20 mg/L, and 50 mg/L) and the median lethal concentration LC50 (125 mg/L). The expression of immune-related genes (Hsp90, Toll-8/Tollo, and defensin) was significantly changed in exposed nurse bees at the field-realistic concentration of flupyradifurone. However, three detoxifying enzyme genes (CYP9Q1, -2, and -3) were not affected by pesticide exposure. Our data suggest that although flupyradifurone had a relatively lower acute oral toxicity than many other common pesticides, exposures to the field-realistic and other sublethal concentrations of flupyradifurone still have cytotoxicity and immune-responsive effects on nurse bees. Therefore, flupyradifurone should be considered for its application in crops.